OCEANIA`S HOP MARKET: STATUS, CHALLENGES AND PROSPECTS - RATOSHNIUK, Tatiana; RATOSHNIUK, Viktor; RATOSHNIUK, Viktor; SOKOLOVA, Alla; YURKIVSKY, Oleksandr; GLADKIH, Oleg (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article provides an in-depth analysis of the key indicators characterizing the hop market in Oceania, focusing primarily on Australia and New Zealand. These countries occupy a distinctive position in the global hop production system, combining innovation, quality, and environmental sustainability. Their hop varieties are globally recognized for their exceptional aroma, diverse flavor palette, and high essential oil content, which makes them especially valuable to craft brewers and international beer producers seeking originality and quality consistency. The geographical and climatic conditions of Oceania — long daylight hours in summer, moderate rainfall, cool winters, and nutrient-rich soils — create ideal prerequisites for the cultivation of high-quality hops with stable yields and minimal dependence on artificial inputs.In recent decades, Oceania has gained a strong reputation as a reliable and dynamic supplier of hops, known for its unique varieties such as Nelson Sauvin, Galaxy, and Motueka, which have significantly influenced global brewing trends. The rise of the craft brewing industry has further enhanced demand for these distinctive hops, creating favorable export prospects and encouraging innovation among local producers. The region’s commitment to sustainable agriculture and biosecurity standards strengthens its competitiveness on international markets and appeals to eco-conscious investors.Nevertheless, the hop industry in Oceania faces several serious challenges. Among them are the effects of global climate change, which threaten to alter traditional cultivation cycles and reduce yields; high production and labor costs; and the limited availability of arable land suitable for expanding hop farms. Moreover, the marketing potential of Oceania hops remains underexploited — insufficient brand development, weak digital presence, and the lack of cohesive communication strategies prevent producers from fully realizing their competitive advantages.Addressing these issues requires a coordinated approach combining governmental support, targeted investments in scientific research, advanced agricultural technologies, and modern marketing infrastructure. It is proven that to attract investors effectively and ensure sustainable growth, hop producers in Oceania must implement a comprehensive strategic framework. Such a strategy should integrate risk management, environmental adaptation, and value chain optimization while emphasizing the distinctive quality and regional identity of their products.
Keywords: market; hops; hop industry; Oceania; supply and demand; challenges